Distillation, on-line RP C18 preconcentration and HPLC-UV-PCO-CVAAS as a new combination for the determination of methylmercury in sediments and fish tissue - Eiden, Ralf; Falter, Ralf; Augustin-Castro, Barbara; Schöler, Heinz Friedrich (Fresenius' journal of analytical chemistry, 1997)
Distillation as a way of sample digestion has been combined with on-line RP C18 preconcentration and HPLC-UV-PCO-CVAAS (high performance liquid chromatography — ultra violet — post column oxidation — cold vapour atomic absorption spectrometry) for the determination of methylmercury at back-ground levels in sediments, soils and fish tissue. To prove the accuracy of this method, it was applied to sediment and fish tissue reference materials. The results correspond with the reference values within their error ranges. Excellent recoveries (92-95%) were obtained for the sediment samples by means of the standard addition method. The standard deviations of the sediment samples were within an acceptable range (7.2-12.5%), those of the fish samples were substantially lower (3.4-5.0%). The detection limit is 0.04 ng/g for 1 g sample weight.